Pododermatitis in Captive and Free-Ranging Greater Flamingos (Phoenicopterus roseus). (November 2015) - Wyss, F.; Schumacher, V.; Wenker, C.; Hoby, S.; Gobeli, S.; Arnaud, A.; Engels, M.; Friess, M.; Lange, C. E.; Stoffel, M. H.; Robert, N.
Pododermatitis is frequent in captive flamingos worldwide, but little is known about the associated histopathologic lesions. Involvement of a papillomavirus or herpesvirus has been suspected. Histopathologic evaluation and viral assessment of biopsies from 19 live and 10 dead captive greater flamingos were performed. Selected samples were further examined by transmission electron microscopy and immunohistochemistry. Feet from 10 dead free-ranging greater flamingos were also evaluated. The histologic appearance of lesions of flamingos of increasing age was interpreted as the progression of pododermatitis. Mild histologic lesions were seen in a 3-week-old flamingo chick with no macroscopic lesions, and these were characterized by Micrococcus -like bacteria in the stratum corneum associated with exocytosis of heterophils. The inflammation associated with these bacteria may lead to further histologic changes: irregular columnar proliferations, papillary squirting, and dyskeratosis. In more chronic lesions, hydropic degeneration of keratinocytes, epidermal hyperplasia, and dyskeratosis were seen at the epidermis, as well as proliferation of new blood vessels and increased intercellular matrix in the dermis. Papillomavirus DNA was not identified in any of the samples, while herpesvirus DNA was seen only in a few cases; therefore, these viruses were not thought to be the cause of the lesions. Poor skin health through suboptimal husbandry may weaken the epidermal barrier and predispose the skin to invasion of Micrococcus -like bacteria. Histologic lesions were identified in very young flamingos with no macroscopic lesions; this is likely to be an early stage lesion that may progress to macroscopic lesions.